Analisis Time–Motion Electronic Customs Declaration (ECD) pada Layanan Bandara Internasional - Baskoro Yudho Sumbogo; Agus Rianto; Jani Kusanti (Nucleus Journal, 2025)
This study examined the effectiveness of the Electronic Customs Declaration system in comparison with the manual customs declaration form used in international airports in Indonesia. The research investigated three operational indicators, namely completion time, input accuracy, and user system usability. Thirty participants consisting of working professionals and university students were asked to complete two declaration scenarios in a controlled environment. Each participant filled out the official paper-based declaration form and then used the digital declaration system. The duration of the completion process was recorded using time–motion procedures, and all errors of input were documented. After both procedures were completed, user evaluation was conducted using the System Usability Scale. The findings showed that the digital declaration significantly reduced the completion time, lowered the number of user errors, and obtained an excellent usability score. The digital form guided the decision-making process, minimized interpretation, and reduced cognitive load during input. The results indicated that digital declaration provided more stable performance and supported faster service delivery, which contributed to smoother passenger processing. The study concluded that the implementation of digital customs declaration has the potential to improve operational effectiveness in airports and to support modern service standards in the public sector.